Epidemiologia espacial da hanseníase no município de Paragominas, Pará - SOARES NETO, Julio Moreira (2019)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae, which mainly affects the skin and peripheral nerves, it can cause physical disabilities and deformities when isn't diagnosed and treated early. Thirty percent of the municipalities of Pará are hyperendemic for leprosy, as is the case of Paragominas, which has a detection rate of 46.98 / 100,000 inhabitants in 2017. To identify the spatial distribution of leprosy cases resident in Paragominas, the cases were mapped using a GPS device with the addresses provided by the Municipal Health Department. The data collected were processed in the QGIS software to elaborate case distribution maps, detection rate by census tracts and heat map. For statistical analysis, the local and global Moran I tests were applied, as well as Kulldorff and Knox scanning for clusters detection using the programs GeoDa, ClusterSeer and PPA. A total of 1047 new cases were reported between 2004 and 2010, 791 resided in the urban area and 91% were mapped. An average of nine cases per census tract was observed (minimum 0 and maximum 33); 76 (95%) of the 80 urban census tracts were classified as hyperendemic. Spatial analyzes showed statistically significant cluster formation (p = 0.001 for I by Moran, Kulldorff and Knox). The Knox test showed 83% of the cases have a space-time connection with another case within 100 meters of radius in the period of 3 years of detection. The spatial distribution of leprosy in Paragominas is heterogeneous, resulting in clusters of high transmission. The results help to understand the dynamics of disease transmission in the municipality, besides contributing to the planning of control actions. In addition, a detailed description of the spatial statistics methods used in this study was made.